Tiotropium in COPD: clinical outcomes and economic evidence - Zaniolo, Orietta; Sacchi, Viola; Dal Negro, Roberto W. (Farmeconomia. Health economics and therapeutic pathways, 2010)
Tiotropium bromide is a once-daily anticholinergic bronchodilator with duration of action of at least 24 hours. In clinical trials, tiotropium has been compared with placebo, ipratropium or salmeterol, the most frequently used long-acting β2 agonist. When compared with ipratropium or placebo in COPD management, tiotropium resulted associated with FEV1, dyspnoea and health-related quality of life (QoL) improvement, along with reduced exacerbation and hospitalisation rates. In comparison to salmeterol, it proved to be superior in terms of lung function improvement and exacerbation risk reduction. Recently, the randomised, double-blind trial UPLIFT showed that 4 years of therapy with tiotropium were associated with improvements in lung function, QoL, and exacerbations, and with an effective reduction of mortality compared with control group in 5,993 patients with moderate to very-severe COPD. These encouraging clinical effects are to be traded against the pharmaceutical cost increase induced by the inclusion of tiotropium in routine care. However, published work indicates that this pharmaceutical cost increase may be totally or partially offset by the reduction in costs needed for exacerbations management and hospitalisations. Depending on the setting analysed, tiotropium is estimated to dominate ipratropium and salmeterol or to be associated with an incremental cost of less than € 2,500 per exacerbation avoided. An Italian model based on UPLIFT data shows that therapy including tiotropium induces an incremental cost of € 6,700 for year of life and of € 7,916 for Quality-adjusted Life Year gained, with respect to routine care alone. These values are much lower than commonly accepted thresholds and than cost/effectiveness results estimated for other long-acting bronchodilators. In conclusion, available evidence suggests that tiotropium may prove an appropriate therapeutic option with a largely affordable cost.